**Simplify: (x – 2) (x + 2) (x**^{2} + 4) (x^{4} + 16)

^{2}+ 4) (x

^{4}+ 16)

**Answer :**

Let us simplify the expression, we get

(x – 2) (x + 2) (x^{4} + 4) (x^{4} +16) = (x^{2} – 4) (x^{4} + 4) (x^{4} + 16)

= [(x^{2})^{2} – (4)^{2}] (x^{4} + 16)

= (x^{4} – 16) (x^{4} + 16)

= (x^{4})^{2} – (16)^{2}

= x^{8} – 256

**More Solutions:**

- Find the value of 8×3 – 27y3 + 90xy + 125.
- If a2 – 1/a2 = 5, evaluate a4 + 1/a4
- Find the relation between p and q.
- Find the value of 2a3 + 2/a3
- If x = 1/(4 – x), find the value of
- Find the value of ¼ (x3 – 1/x3)
- Find the value of x3 – 1/x3
- Find the value of x3 – 1/x3
- Find the sum of their squares.
- If a – b = 7 and a3 – b3 = 133, find:
- Find the coefficient of x2 expansion of